2012
DOI: 10.7162/s1809-97772012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tinnitus in elderly individuals with and without history of occupational noise exposure

Abstract: Summary Introduction: The various metabolic and circulatory alterations that are related to noise exposure may cause the onset of several symptoms, including tinnitus. Objective: The purpose of the study was to assess the prevalence of tinnitus complaints in elderly individuals with and without history of occupational noise exposure. Method: This prospective study was conducted in a sample population consisting of 502 individuals aged over 60 years, by anamnesis and audiological evaluation. The variables that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…These results are similar to those of previous studies, 14 19 which also found a prevalence of sensorineural HL, with an association between HL and DM or hypertension in populations of different ages, but especially among the elderly. 8 9 10 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those of previous studies, 14 19 which also found a prevalence of sensorineural HL, with an association between HL and DM or hypertension in populations of different ages, but especially among the elderly. 8 9 10 30 …”
Section: Discussionmentioning
confidence: 99%
“… 7 Hearing loss, tinnitus and vertigo are associated with smoking, high blood pressure (hypertension), diabetes mellitus (DM), lifestyle, age, health history, leisure activities and exposure to occupational noise, and the incidence of auditory symptoms seems correlated with noise exposure during life. 8 9 10 11 12 13…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the elderly, various metabolic and circulatory disorders that may be associated with exposure to occupational noise can cause various symptoms such as hearing loss, vertigo, and tinnitus. [ 3 8 9 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus affects about one fifth of the general public and one in three of the elderly population and is seen in the ages from 40 to 80 [24]. While many factors have been blamed for the pathophysiology and causes of tinnitus, its etiology has not been completely elucidated [25].…”
Section: Discussionmentioning
confidence: 99%